Makna al-Miṣbāḥ Perspektif Imam Fakhruddīn al-Rāzī Dalam Tafsir Mafātīḥ al-Ghayb - Wilda Wulandari; Ahmad Zuhri; Harun al-Rasyid (Kamaya: Jurnal Ilmu Agama, 2025)
This study examines the symbolic meaning of al-Miṣbāḥ (lamp) in the Qur'an with a focus on the interpretation of Imam Fakhruddīn al-Rāzī in his monumental work, Tafsir Mafātīḥ al-Ghayb. In contrast to previous studies that tended to interpret al-Miṣbāḥ textually, this study offers novelty by integrating linguistic-semantic analysis into classical interpretation methodologies. The aim is to reveal the multidimensional meaning of al-Miṣbāḥ, both as a singular symbol (miṣbāḥ) that symbolizes the light of divine guidance in the believer's heart (QS. an-Nūr: 35), and as a plural symbol (maṣābīḥ) that represents cosmic beauty and protection (QS. al-Mulk: 5 and QS. Fuṣṣilat: 12). The method used is a qualitative study based on library research, with a thematic approach (tafsīr mawḍū'ī) that is integrated with linguistic and semantic analysis. This study found that al-Miṣbāḥ not only serves as a physical symbol, but also represents the radiance of revelation that guides humans intellectually and spiritually. al-Rāzī's interpretation shows the methodological depth of associating the symbol of light with the awareness of faith and the purpose of human life within the framework of the Islamic worldview.